Investigation and analysis of communication status and training needs between ICU nurses and patients' families - LI Zun-zhu, LI Zhen, ZHANG Yuan-yuan, LIU Jin-bang, LUO Hong-bo, HE Huai-wu, LONG Yun (Jichu yixue yu linchuang, 2020)
Objective To investigate the learning needs of communication training between Intensive Care Unit(ICU) nurses and patients families in Peking Union Medical College Hospital. Methods The Department of Critical Care Medicine of Peking Union Medical College Hospital distributed questionnaires to 143 nurses working in the department, and scored whether nurses had negative experience in communicating with patients'families, confidence in building harmonious relationship and the need for training. Results A total of 138 questionnaires were obtained. 46.4% of nurses in ICU think they sometimes or often encounter negative experiences in their work. Only 30.4% of nurses were very confident or confident in their communication skills. As much as 83.3% of nurses believed that they should be trained in communication with patients family members. Conclusions Communication training is very important for intensive care nurses.